Intrinsic variation of the polarization-resolved SHG from collagen: Multiscale analysis and application to parchments - Giulia Galante; Laurianne Robinet; Sylvie Heu-Thao; Clément Caporal; Gaël Latour; Marie-Claire Schanne-Klein (APL Photonics)
Second harmonic generation (SHG) microscopy is nowadays the gold standard technique for collagen structural imaging in intact tissues with sub-micrometer resolution. This multiphoton modality can be combined with polarimetry to provide key information about the 3D hierarchical organization of collagen. Notably, the so-called anisotropy parameter processed from polarization-resolved SHG (P-SHG) has been shown to vary with the orientational disorder of the fibrils within the focal volume and with their out-of-plane orientation. However, analytical equations describing both effects within the same formalism are still lacking. In this work, we present a unified multiscale theoretical approach of the intrinsic variations of the anisotropy parameter. We then measure these variations in the very same collagen samples to ensure reliable comparisons. To that end, we use parchments, which are materials made from animal skins and which contain almost exclusively collagen. These parchments are manufactured in different ways to obtain different collagen distributions. Our series of measurements exhibit a good agreement with our theoretical approach, which shows the relevance of P-SHG measurements to probe collagen multiscale organization in tissues.